Peningkatan Potensi Ibu Rumah Tangga dalam Mengolah Sampah Organik Rumah Tangga Menggunakan Metode Takakura di Desa Cibiru Wetan, Kabupaten Bandung - Soni Muhsinin; Deden Indra Dinata; Ivan Andriansyah; Aiyi Asnawi (Jurnal Pengabdian Pada Masyarakat, 2019)
INCREASING OF HOUSEWIVES POTENTIAL IN PROCESSING DOMESTIC ORGANIC WASTE BY USING TAKAKURA METHOD IN CIBIRU WETAN VILLAGE, BANDUNG REGENCY. Domestic waste (DW) is a major environmental challenge for many urban local bodies in Indonesia both in the village and in the city, where urbanization, industrialization and economic growth have resulted in increased waste generation per person. One way to solve this waste is to turn organic domestic into compost. Composting, the recycling of organic waste such as vegetation and food waste reduces the amount of waste going to landfill and is, therefore, a rapidly growing sector. Desa Cibiru Wetan, Kab. Bandung, West Java is one of the villages that has learned about how to process organic waste into compost and become a pilot project but because of the distance between raw materials and management with compost incubator so that compost production is disturbed. Therefore, the purpose of the project activity was to produce compost from domestic organic waste by the Takakura method. In this method, a small incubator was used and placed at the home of the community. Although on a small scale but with many multipliers, it able to produce an abundant compost and can be an alternative for the existing compost incubator method. The stage included counseling and socialization, training in making incubator Takakura, training in production compos,t and monitoring and evaluation. The results showed a good understanding of both groups for both the socialization and counseling stages as well as for the practice of production of compost. In conclusion, the activity on the production of compost by using Takakura method able was to solved for domestic organic waste and remind set the interest of the community in producing compost.